2016
DOI: 10.1111/hex.12448
|View full text |Cite
|
Sign up to set email alerts
|

Group affiliation in self‐management: support or threat to identity?

Abstract: BackgroundSelf‐management is considered important in chronic illness, and contemporary health policy recommends participation in support groups for individuals with chronic conditions. Although withdrawal from or non‐participation in support groups is an important problem, there is limited knowledge about individuals' own motivation for participation in or withdrawal from self‐management support groups.ObjectivesTo investigate how individuals with type 2 diabetes perceive participation in group‐based self‐mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
(91 reference statements)
0
13
0
4
Order By: Relevance
“…While this may be difficult to address, more research is needed to ascertain the needs and experiences of these participants. Bossy et al [77], in a recent study looked at attendees and non-attendees of group diabetes programmes and found a divergence between those wanting to be with similar others and those who formed an identity around coping on their own. This is an important new line of inquiry that requires further exploration.…”
Section: Structural Limitationsmentioning
confidence: 99%
“…While this may be difficult to address, more research is needed to ascertain the needs and experiences of these participants. Bossy et al [77], in a recent study looked at attendees and non-attendees of group diabetes programmes and found a divergence between those wanting to be with similar others and those who formed an identity around coping on their own. This is an important new line of inquiry that requires further exploration.…”
Section: Structural Limitationsmentioning
confidence: 99%
“…Continued exchange among peers is important for individuals to feel less alone while engaging in chronic illness self-management and to generate knowledge that is based on personal experiences [35]. However, frequent interaction with peers may often not be feasible because of spatiotemporal limitations or fears of stigmatization in face-to-face environments.…”
Section: Discussionmentioning
confidence: 99%
“…The group‐based approaches vary in content and may include a mix of the following group pedagogic measures: expert‐patient tutoring; discussions between leaders and participants; educational components; and content such as nutrition advice and physical activities, the latter of which could be described as a lifestyle‐oriented approach . The Norwegian structure of group‐based support ranges from public, professionally led groups to private nonprofit layperson‐driven groups, and local physical activity and nutrition programmes may be both professionally and layperson‐driven . In other countries, self‐management support is primarily based on initiatives from volunteer and patient organizations …”
Section: Introductionmentioning
confidence: 99%